2020
DOI: 10.1016/j.dental.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Monomer release from direct and indirect adhesive restorations: A comparative in vitro study

Abstract: Significance. In terms of monomer release, indirect restorations are a good alternative to direct restorations to limit patient exposure to residual monomers. It is important to ideally design the fit of indirect restoration so that the cement layer is as thin as possible and the monomer release from this cement layer remains as low as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
(17 reference statements)
1
15
0
2
Order By: Relevance
“…The control analysis was performed by HPLC-MS/MS calibrated with d16BPA as the internal standard. This analytical method is well established in recent literature [49][50][51] and is recommended by Hope et al [45]. The concentrations measured using HPLC-UV/Vis could not be reproduced as the amount of BPA detected was below the LOQ of 0.03 ng mL -1 .…”
Section: Discussionmentioning
confidence: 99%
“…The control analysis was performed by HPLC-MS/MS calibrated with d16BPA as the internal standard. This analytical method is well established in recent literature [49][50][51] and is recommended by Hope et al [45]. The concentrations measured using HPLC-UV/Vis could not be reproduced as the amount of BPA detected was below the LOQ of 0.03 ng mL -1 .…”
Section: Discussionmentioning
confidence: 99%
“…46 Moreover, high content of unreacted monomer facilitates its release to body environment, limiting material biocompatibility and increasing cytotoxicity. 52,53 In the study conducted by Melo et al, instrument lubrication with SBMP caused reduction in the degree of conversion of all examined composites. Usage of ASB as a lubricant also decreased the degree of conversion for Empress Direct (Ivoclar Vivadent, Schaan, Liechtenstein) A2 and Bleach shades however increased it for Esthet X HD (Dentsply Caulk, Milford, Delaware, United States) A2 shade.…”
Section: Polymerization Qualitymentioning
confidence: 89%
“…The latter might be more stable in terms of monomer delivery and therefore might be more biocompatible. 30 For instance, a study assessed the osseointegration of PMMA implants placed in a mongrel dog for a period of 24 months, 31 and the authors concluded that clinically and histologically, the PMMA plastic implants were bioacceptable, displayed functional stability (due to their shape, size and technical design), and were successfully osseointegrated. Another study found the formation of the basal membrane and of hemidesmosomes two weeks after the placement of endosseous epoxy resin dental implants in dogs.…”
Section: Effects Of the Materialsmentioning
confidence: 99%